Utilizing PLEASE Strategy as a Metacognitive Writing Process in Teaching Writing a Recount Text toward Students’ Writing Skills and Motivation - Utami, Diana Puji; Yundayani , Audi; Puspitasari , Maya (STAIN Sultan Abdurrahman Kepulauan Riau, 2025)
Writing is a process-oriented language skill requiring students to construct and develop ideas and thoughts in written form. This study was designed to investigate whether there is an effect of PLEASE strategy on students’ writing skills and motivation to recount texts among 11th-grade students. This study employed a quasi-experimental design on both experimental and control classes. The data were collected through writing tests to measure writing skills and a writing motivation questionnaire to analyze writing motivation. The data were analyzed statistically using a t-test after complying with Normality and Homogeneity test. The results revealed that PLEASE strategy affected student’s writing skills and motivation to recount texts compared to teacher-centered strategy. PLEASE strategy promoted a metacognitive skill within the writing process on recount texts. This was favorable to assist the students in planning, monitoring, and evaluating writing through the steps of Pick, List, Evaluate, Activate, Supply, and End, and motivate the students to write extrinsically and intrinsically. This study recommended broader implementation of PLEASE strategy to teach the writing process across other text genres in all stages of education.